2021
DOI: 10.3390/nano11061484
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Activity, Cytotoxicity, and Antimicrobial Effects of Human Albumin- and Polysorbate-80-Coated Silver Nanoparticles

Abstract: In this study, we aimed to develop a technique for colloidal silver nanoparticle (AgNP) modification in order to increase their stability in aqueous suspensions. For this purpose, 40-nm spherical AgNPs were modified by the addition of either human albumin or Tween-80 (Polysorbate-80). After detailed characterization of their physicochemical properties, the hemolytic activity of the nonmodified and modified AgNPs was investigated, as well as their cytotoxicity and antimicrobial effects. Both albumin- and Tween-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The results show that the AgNPs, even at high concentration, have little hemolytic activity. Korolev et al [ 51 ] and Zharkova and team [ 52 ] obtained similar results. They found that the hemolytic activity of unmodified AgNPs was minimal and did not exceed a few percent.…”
Section: Resultssupporting
confidence: 54%
“…The results show that the AgNPs, even at high concentration, have little hemolytic activity. Korolev et al [ 51 ] and Zharkova and team [ 52 ] obtained similar results. They found that the hemolytic activity of unmodified AgNPs was minimal and did not exceed a few percent.…”
Section: Resultssupporting
confidence: 54%
“…First, we briefly explain the reasons why it was impossible to include the results of the four publications in Table 1 . These reasons are: the concentration of AgNPs for which hemolysis was measured is not indicated [ 74 ], hemolysis data are presented in mg/dL without indication of initial erythrocyte concentration [ 75 ], data of AgNPs are presented in µM (it is impossible to convert it to µg/mL due to the fact that AgNPs are not molecules) [ 76 ], and hemolysis data presented in the description and in corresponding figures are inconsistent (with a ten-fold difference) [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, proteins such as CX3CR1, CSF-1R, CX3CL1 and CSF-1 in Fe 3 O 4 -siPD-L1@M -BV2 were detected by western blot [ 37 ]. The hemolysis of Fe 3 O 4 -siPD-L1@M -BV2 was investigated by using rat erythrocytes [ 43 ]. The release of siPD-L1 from Fe 3 O 4 -siPD-L1@M -BV2 in GSH-containing solution was observed by gel retardation assay [ 44 ].…”
Section: Methodsmentioning
confidence: 99%